Level of Exclusivity and Inclusivity of Indonesian Students in Malaysia - Mukharrom, Tamyiz; Roy Purwanto, Muhammad; Mahfudz, Mahsun; Supriadi, Supriadi (Opción, 2019)
This paper intends to look at the level of inclusiveness and exclusivity of Indonesian students in Malaysia. There are around 11,000 (eleven thousand) Indonesian students in Malaysia studying from the S1-S3 level. Indonesian students as much as that certainly tend towards religious mindset, there are inclusive and exclusive. This research tries to see which direction Indonesian students are in Malaysia. This research is a quantitative study, with a sample of Indonesian students residing in Malaysia. The sample consisted of 100 re- spondents from a total of 11 thousand populations. Respondents were asked questions about Islam, religious views, religious attitudes, religious violence, and the concept of jihad. Based on these questions we can see the tendency of exclusivity or inclusiveness of Indonesian students in Malaysia. The results of this study indicate that 100% of Indonesian students in Malaysia consider that Islam is the religion of rahmatan lilalamin. The 100% also reject jihad with violence as carried out by ISIS. Aside from the inclusive opinion, they also think that it is exclusive because there are 7% of Indonesian pursuers in Malaysia who consider that the perpetrators of major sins, such as adultery, killing are infidels. There are also 3% who consider democracy and human rights incompatible with Islam.